Diversity and inclusion information: Cisco - Sutton, Kyra Leigh (Henry Stewart Talks, 2022)
Cisco’s EOE statement and job postings are analyzed as examples of how job seekers may evaluate organizations’ diversity and inclusion policies, and how companies can use such tools to attract a diverse group of candidates in turn.